How to beat COVID-19: Know your enemy well - Santiago Herrero (World Nutrition Journal, 2020)
Anyone is at risk of contracting COVID-19 if exposed to the virus. Some people are more likely to become seriously ill than others, which means they may need hospitalization, intensive care, or respiratory support (respirator mask, high flow oxygen therapy, ventilators, etc.), and some may even die, mainly by severe respiratory failure. Those patients with asthma (moderate to severe), cardiovascular disease, cystic fibrosis, hypertension, immunosuppression, liver disease, pregnancy, smoker, thalassemia and diabetes (especially type 1) have a higher risk of getting sick and suffering the disease with more virulence and potential mortality. The older people are in risk because the chronical diseases and comorbidities are associate with the aging.This presentation aims to explain the mechanisms of infection and inflammation by the coronavirus in order to act primarily on them. If you know your enemy well, you can treat it from an etiopathogenic perspective.